PRODUKSI SELULASE KASAR DARI KAPANG TRICHODERMA VIRIDE DENGAN PERLAKUAN KONSENTRASI SUBSTRAT AMPAS TEBU DAN LAMA FERMENTASI - GUNAM, IDA BAGUS WAYAN; ARYANTA, WAYAN REDI; DARMA, IDA BAGUS N. SURYA (Jurnal Biologi Udayana; Vol 15 No 2 (2011): Jurnal Biologi, 2011)
This research was done in order to utilize bagasse as substrates to produce crude cellulase from Trichoderma viride. This research used a randomized block design with factorial pattern which consisted of two factors. The first factor was the concentration of substrate which consisted of three levels namely, substrate concentration of 1%, 2%, and 3%. The second factor was the fermentation time which consisted of three levels namely, 5, 7, and 9 days. Each treatment classified into two groups based on time of production. The results showed that the concentration of bagasse and fermentation time significantly influenced the parameters observation of crude cellulase production from Trichoderma viride. The optimal treatment combination to produce crude cellulase with maximum activity was the treatment of 3% substrate concentration and fermentation time of 7 days with an average value of cellulase activity (filter paperase), soluble protein, and cellulase specific activity were 0.771 Unit/mL, 0.262 mg/mL, and 2.940 Unit/mg, respectively.
Keywords: bagasse; Trichoderma viride; fermentation; cellulase